Ginsenoside Rg3 Attenuates TNF-α-Induced Damage in Chondrocytes through Regulating SIRT1-Mediated Anti-Apoptotic and Anti-Inflammatory Mechanisms - Ching-Hou Ma; Wan-Ching Chou; Chin-Hsien Wu; I-Ming Jou; Yuan-Kun Tu; Pei-Ling Hsieh; Kun-Ling Tsai (Antioxidants, 2021)
The upregulation of tumor necrosis factor-alpha (TNF-α) is a common event in arthritis, and the subsequent signaling cascade that leads to tissue damage has become the research focus. To explore a potential therapeutic strategy to prevent cartilage degradation, we tested the effect of ginsenoside Rg3, a bioactive component of Panax ginseng, on TNF-α-stimulated chondrocytes.TC28a2 Human Chondrocytes were treated with TNF-α to induce damage of chondrocytes. SIRT1 and PGC-1a expression levels were investigated by Western blotting assay. Mitochondrial SIRT3 and acetylated Cyclophilin D (CypD) were investigated using mitochondrial isolation. The mitochondrial mass number and mitochondrial DNA copy were studied for mitochondrial biogenesis. MitoSOX and JC-1 were used for the investigation of mitochondrial ROS and membrane potential. Apoptotic markers, pro-inflammatory events were also tested to prove the protective effects of Rg3. We showed Rg3 reversed the TNF-α-inhibited SIRT1 expression. Moreover, the activation of the SIRT1/PGC-1α/SIRT3 pathway by Rg3 suppressed the TNF-α-induced acetylation of CypD, resulting in less mitochondrial dysfunction and accumulation of reactive oxygen species (ROS). Additionally, we demonstrated that the reduction of ROS ameliorated the TNF-α-elicited apoptosis. Furthermore, the Rg3-reverted SIRT1/PGC-1α/SIRT3 activation mediated the repression of p38 MAPK, which downregulated the NF-κB translocation in the TNF-α-treated cells. Our results revealed that administration of Rg3 diminished the production of interleukin 8 (IL-8) and matrix metallopeptidase 9 (MMP-9) in chondrocytes via SIRT1/PGC-1α/SIRT3/p38 MAPK/NF-κB signaling in response to TNF-α stimulation. Taken together, we showed that Rg3 may serve as an adjunct therapy for patients with arthritis.